Kesantunan Komunikasi Pada Media Cetak Elektronik Sebagai Pembentuk Integritas Pembaca - Kendek, Martina Asri; Gasong, Dina; Simega, Berthin (CV. ITTC INDONESIA, 2024)
The aim of this research is to describe positive and negative politeness strategies based on Brown and Levinson's theory of politeness and how polite communication in electronic print media forms reader integrity. The research was conducted as a qualitative type of research. Data collection procedures were carried out using reading techniques, note-taking techniques and documentation techniques. The data analysis method was carried out in four stages, namely data collection, data reduction, data presentation, and verification and conclusions. The results of this research show that communication politeness in electronic print media uses fifteen positive politeness strategies and eight negative politeness strategies. The fifteen positive politeness strategies and eight negative politeness strategies used by the three electronic print media consisting of detiknews.com, kompas.com, and tribunnews.com, namely speakers and readers (listeners/readers) are marked with words, phrases, clauses, and sentences on electronic print media. The politeness of communication in electronic print media used by the three electronic print media consisting of detiknews.com, kompas.com, and tribunnews.com, as forming the integrity of readers, is marked in words, phrases, clauses and sentences, namely being critical, creative, excel, and be responsible for oneself, the environment, family, and apply it in everyday life.